Anxiety, depression, and social connectedness among the general population of eight countries during the COVID-19 pandemic - Di Long; Gouke J. Bonsel; Erica I. Lubetkin; Mathieu F. Janssen; Juanita A. Haagsma (Archives of Public Health, 2022)
Abstract Background The COVID-19 pandemic affected the mental health of the general population through multiple pathways. The aim of this study was to examine anxiety, depression, self-confidence, and social connectedness among the general population of eight countries during the COVID-19 pandemic, their underlying factors, and vulnerable groups. Methods A web-based survey was administered to persons from the general population of China, Greece, Italy, Netherlands, Russia, Sweden, the United Kingdom, and the United States. The survey included the Generalized Anxiety Disorder-7 (GAD-7), Patient Health Questionnaire-9 (PHQ-9) and items on self-confidence, social connectedness, and socio-demographics. Data were analyzed with descriptive statistics, exploratory factor analysis and regression analysis. Results Twenty-three thousand six hundred twenty-two respondents completed the survey. Overall, 42% of the total sample had mild to severe anxiety symptoms and 43% had mild to severe depression symptoms. 14% to 38% reported suboptimal ratings in self-confidence, social participation, contact with family and friends, and feeling connected to others. In the exploratory factor analyses, in most countries, one dominant factor had a high influence on GAD-7, PHQ-9 sum scores and self-confidence with eigenvalue (% variance) above 3.2 (53.9%). One less dominant factor had a high influence on social connectedness scores with eigenvalue (% variance) ranging above 0.8 (12.8%). Being younger, female, having chronic conditions, perceived as risky to COVID-19 infection, and feeling not very well protected against COVID-19 were significantly associated with the two underlying factors. Conclusions Anxiety, depression, and problems with self-confidence and social connectedness were highly prevalent in the general population of eight countries during the early phase of the COVID-19 pandemic. This highlights the importance of the allocation of additional resources to implement policies to mitigate the impact of the pandemic on mental health.